2020
DOI: 10.1186/s12885-020-07016-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neoadjuvant and adjuvant immunotherapy on the survival of pancreatic cancer patients: a retrospective analysis

Abstract: Background: Immunotherapy has become an essential part of cancer treatment after showing great efficacy in various malignancies. However, its effectiveness in pancreatic ductal adenocarcinoma (PDAC), especially in resectable pancreatic cancer, has not been studied. The primary objective of this study is to compare the OS impact of immunotherapy between PDAC patients who receive neoadjuvant immunotherapy and patients who receive adjuvant immunotherapy. The secondary objective is to investigate the impact of neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…However, recurrence rates even after R0 resection remain unacceptably high [6][7][8][9][10]. The integration of more efficacious systemic chemotherapy regimens has improved median overall survival [11], yet responses of individual PDACs to chemotherapy are highly heterogeneous and personalization of perioperative therapy is in its infancy [12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…However, recurrence rates even after R0 resection remain unacceptably high [6][7][8][9][10]. The integration of more efficacious systemic chemotherapy regimens has improved median overall survival [11], yet responses of individual PDACs to chemotherapy are highly heterogeneous and personalization of perioperative therapy is in its infancy [12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that patients with PDCA could benefit from adjuvant chemotherapy plus immunotherapy. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in the neoadjuvant subset analysis, immunotherapy was associated with significantly improved OS compared to no immunotherapy. 33 Moreover, neoadjuvant immunotherapy may increase the presence of TILs in the PC microenvironment 34 and reduce the immunosuppressive effects of surgery by systemic release of glucocorticoids which induce apoptosis of naïve T cells and suppression of T-cell proliferation. 35 , 36 Together these limit the probability of recurrence.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%